HUBUNGAN KEPEMIMPINAN DIRI DENGAN MANAJEMEN KONFLIK PADA MAHASISWA YANG AKTIF DALAM ORGANISASI KEMAHASISWAAN - Evangelista Rochadi; A. Setyandari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
One goal of this research is to find out how much self-leadership and conflict management skills students in Sanata Dharma University's Department of Education and FKIP have. Another two goals are to find out how much conflict management skills students have and how self-leadership and conflict management relate to each other. Facing complicated organizational of students dynamics requires self-leadership and conflict management abilities, which is why this research is driven by such needs. The methodology of this investigation is based on quantitative correlations. A total of 116 students were chosen for the study by use of a purposive selection approach. Two validated and reliable surveys, one on self-leadership and the other on conflict management, were used to gather data. Using the Spearman correlation test, the data were evaluated. According to the study's findings, there is a strong and positive correlation between self-leadership and conflict management, with a correlation coefficient of 0.996 and a p-value less than 0.001. This suggests that the capacity to handle conflicts effectively increases in direct correlation with one's degree of self-leadership.